2016
DOI: 10.1136/neurintsurg-2016-012518
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing procedure times with a standardized approach to ELVO cases

Abstract: Background Embolectomy is the standard of care for emergent large vessel occlusion (ELVO), and needs to be done as quickly as possible for the best possible outcomes. Optimization of workflow and process is certainly paramount. One aspect of this is process improvement to standardize as much as possible the procedure in order to decrease variability among operators, which breeds familiarity for the entire team. Objective To evaluate the impact of a standardized approach to ELVO cases in decreasing times from g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 11 publications
2
14
0
Order By: Relevance
“…One advantage that operators consistently appreciated was the ability to use distal access catheters due to its larger inner diameter. The time from groin puncture to recanalization was similar to that reported by ADAPT FAST, perhaps due to a higher FPE, a less complex patient population, or use of only one standard approach, which has been reported by McTaggart et al [17] to improve procedure times.…”
Section: Discussionsupporting
confidence: 64%
“…One advantage that operators consistently appreciated was the ability to use distal access catheters due to its larger inner diameter. The time from groin puncture to recanalization was similar to that reported by ADAPT FAST, perhaps due to a higher FPE, a less complex patient population, or use of only one standard approach, which has been reported by McTaggart et al [17] to improve procedure times.…”
Section: Discussionsupporting
confidence: 64%
“…Additional technical variations and standardized approaches have been reported in the literature noting particular retrieval techniques and/or combinations of reperfusion catheters and stent retrievers 69–73. Whichever techniques are used, standardized approaches can minimize the risk and maximize speedy recanalization 74 . Therefore, in comparing currently available techniques, the superiority of stent retrievers versus thromboaspiration alone, versus combinational techniques, has not been clearly established.…”
Section: Technical Considerationsmentioning
confidence: 99%
“…Clinical outcomes, demonstrated by studies, are heavily reliant on reperfusion times (2,3). In managing AIS cases due to large vessel occlusion, the goal has been to achieve rapid recanalization and to reduce time from onset to mechanical thrombectomy (MT) (4,5). Optimal practices to generate improvement of effective and efficient case management remains immature and lacks a complete consensus, despite technological advancements in managing workflow.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that modifications and improvements are potentially attainable at every stage of the care workflow, where considerable emphasis has been placed to reduce transport times (4,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). The quality of care in AIS has been shown to be influenced by operational modifications such as the implementation of evidence-based stroke protocols, improved staff education and training, and prioritization of hospital resources (17,18).…”
Section: Introductionmentioning
confidence: 99%